Archaeological approaches to market exchange in ancient societies - Garraty, Christopher P., 1971-; Stark, Barbara L. (University Press of Colorado, 2010)
"Market activities were central to the economies of many ancient societies, yet they have received little research from the archacological community. Arcaeological Approaches to Market Exchange in Ancient Societies is the first book to address the development, change, and organizational complexity of ancient markets from a comparative archaeological perspective." "Drawing from historical documents and archacological records from Mesoamerica, the U.S. Southwest, East Africa, and the Andes, this volume reveals the complexity of ancient market place development and economic behavior in both hierarchical and non-hierarchical societies. Highlighting four principal themes---the defining characteristies of market exchange; the recognition of market exchange archaeologically; the relationship among market, political, and other social institutions; and the conditions in which market systems develop and change---the book contains a strong methodological and theoretical focus on market exchange." "Diverse contributions from noted scholars show the history of market exchange and other activities to be more dynamic than scholars previously appreciated. Archaeological Approaches to Market Exchange in Ancient Societies will be of interest to archaeologists, anthropologists, material-culture theorists, economists, and historians"--Jacket